REFLECTIVE TEACHING AMONG INDONESIAN NOVICE EFL TEACHERS: HINDRANCES TO THE PRACTICE - Ningsih, Yohana Dian Rahayu; Lengkanawati, Nenden Sri (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2023)
Research and studies on teachers’ reflective practice have increased over the decades. However, the factors contributing to the low levels and application of reflective practice among Indonesian novice EFL teachers have been very little explored. This study aims to explore the hindrances faced by novice EFL teachers to their practice of reflective teaching. This qualitative study used a survey method and an online questionnaire adopted and developed from the IETRTQ or Inhibitors to EFL Teachers’ Reflective Teaching Questionnaire as the research instrument. The questionnaire was then administered to 30 Indonesian novice EFL teachers as the samples of this study. After collecting the data, simple descriptive statistics such as mean and frequency analysis were employed to provide a more qualitative analysis regarding the result. The findings of this study show that the lack of novice EFL teachers’ reflective practices is due to some hindrances to their practice. The hindrances include a lack of knowledge factors, emotional and affective factors, and institutional factors. Further, it is expected that novice teachers, EFL study programs, EFL policy makers and trainers, teaching institutions, and future researchers can work cooperatively to contribute to the implementation of reflective practice of teaching.